Histologic and Histomorphometric Comparison of Bone Regeneration Between Bone Morphogenetic Protein-2 and Platelet-Derived Growth Factor-BB in Experimental Groups. Issue 3 (May 2016) - Guven, Gokhan; Gultekin, B. Alper; Guven, Gamze Senol; Guzel, Elif; Furat, Selenay; Ersanli, Selim
Abstract : Abstract: Efficacy of recombinant human bone morphogenetic protein-2 (rhBMP-2) and recombinant human platelet-derived growth factor-BB( rhPDGF-BB) delivered via absorbable collagen sponge (ACS) on bone formation was evaluated in guinea pig tibias. Three-millimeter-circular bone tibia defects were created in 24 guinea pigs assigned randomly to 4 groups according to the following defect filling materials: ACS only, rhBMP-2+ACS, rhPDGF-BB+ACS, or empty. New bone formation was evaluated histologically and histomorphometrically at 15 (early healing) and 45 days (late healing). Mean new bone per total defect area ratio was 0.73, 0.57, 0.43, and 0.42 in rhBMP-2+ACS, rhPDGF-BB+ACS, ACS only, and empty groups at early healing, respectively. During early healing, significantly more new bone formation was observed in rhBMP-2+ACS and rhPDGF-BB+ACS groups than in the control groups. New bone formation was significantly higher with rhBMP-2+ACS than with rhPDGF-BB+ACS. Mean new bone per total defect area ratio was 0.81, 0.86, 0.74, and 0.75 in the rhBMP-2+ACS, rhPDGF-BB+ACS, ACS only, and empty groups at late healing, respectively. During late healing, new bone formation was significantly higher in the rhPDGF-BB+ACS group relative to both control groups, but the results did not differ significantly from those in the rhBMP-2+ACS group. New bone formation in the rhBMP-2+ACS group did not change significantly between the healing periods. In the rhPDGF-BB+ACS group, however, new bone formation was significantly higher in the late healing period. Both growth factors accelerated new bone formation in the early healing period. Although rhBMP-2 was more effective in the early healing period, the effects of rhPDGF-BB were longer lasting.